First-order and higher-order inflation expectations: Evidence about households and firms - Pascal Kieren; Christian König-Kersting; Robert J. Schmidt; Stefan T. Trautmann; Franziska Theurich (Deutsche Bundesbank, 2024)
We study first-order and higher-order inflation expectations of German households and firms elicited from surveys. The data allows to shed light on the relation between different orders of beliefs, and to derivate implications for noisy-information models with infinite regress. Moreover, since the elicited data is identical for households and firms, it also allows studying whether the relation between first-order and higher-order beliefs differs between the two samples. While we find that this relation is mostly identical between households and firms in our data, we identify differences to previously elicited data in the literature. We discuss potential sources for these differences and their theoretical implications.
Keywords: D84; E31; G17; 330; Inflation expectations; higher-order beliefs; noisy-information models; surveys